The Effect of Capital Adequacy Ratio, Loan-to-Deposit Ratio, Non-Performing Loans, and Operating Expenses on Operating Income and Bank Stability Among Banking Companies Listed on the Indonesian Stock Exchange Period 2022–2024 - Dewi, Dewi; Sunny, Sunny; Wijaya, Suherni; Ria Sitorus, Paskah; Lidia Gultom , Lamtiur (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to identify factors influencing the stability of banks listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. This research employs a quantitative approach using secondary data derived from annual financial reports of 46 banking companies, resulting in 138 observations. The data were analyzed using multiple linear regression analysis, preceded by classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The results show that the Capital Adequacy Ratio (CAR) and the Operating Expenses to Operating Income ratio (BOPO) have a negative and significant effect on bank stability. Meanwhile, the Loan to Deposit Ratio (LDR) and Non-Performing Loans (NPL) do not have a significant effect on bank stability. Simultaneously, CAR, LDR, NPL, and BOPO have a significant influence on bank stability. In conclusion, banking stability is determined by the combined performance of financial ratios, particularly capital management and operational efficiency. Therefore, banks are required to optimize the management of these factors in order to maintain financial stability and enhance resilience against economic uncertainty